Ginsenoside in the treatment of type 2 diabetes and its complications: a promising traditional chinese medicine - Liu, Yingying; Ju, Yang; Wang, Yanjun; Cui, Xiaoyan; Sun, Yunwei; Hu, Ping; Chen, Yan (Frontiers in Pharmacology, 2025)
Type 2 diabetes mellitus (T2DM), a chronic condition commonly observed in adults, particularly among the elderly, is characterized by a dysfunctional insulin response that impairs blood glucose regulation, resulting in persistent hyperglycemia. Ginseng, a medicinal plant with significant economic value and a longstanding history of therapeutic use in Asia, has shown efficacy against various diseases. Extensive clinical and experimental studies highlight ginsenosides, its primary bioactive compounds, for their multiple therapeutic effects across a range of conditions, including endocrine, cardiovascular, and central nervous system disorders. Various ginsenoside types have demonstrated potential in lowering blood glucose levels, reducing insulin resistance, and alleviating complications through the modulation of key protein targets and signaling pathways. This review consolidates the pharmacological actions and mechanisms of distinct ginsenosides in managing diabetes and its complications, offering a theoretical foundation for further pharmacological research and novel drug development for T2DM treatment, while also providing robust theoretical support for future clinical applications.